2010
DOI: 10.1126/science.1186799
|View full text |Cite
|
Sign up to set email alerts
|

Washing Away Postdecisional Dissonance

Abstract: After choosing between two alternatives, people perceive the chosen alternative as more attractive and the rejected alternative as less attractive. This postdecisional dissonance effect was eliminated by cleaning one's hands. Going beyond prior purification effects in the moral domain, physical cleansing seems to more generally remove past concerns, resulting in a metaphorical "clean slate" effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 5 publications
5
116
1
3
Order By: Relevance
“…The reason why this probability should depend on both opinions is that, usually an opinion includes prejudices about differing points of view (this is strongly related with the idea of cognitive dissonance in psychology [16][17][18]). This generalization allows for complex interactions among the opinions in an unified way and can be seen as a generalization of the bounded confidence rules [3,4], as those rules can be recovered as special cases.…”
Section: The Sznajd Model With Confidence Rulesmentioning
confidence: 99%
“…The reason why this probability should depend on both opinions is that, usually an opinion includes prejudices about differing points of view (this is strongly related with the idea of cognitive dissonance in psychology [16][17][18]). This generalization allows for complex interactions among the opinions in an unified way and can be seen as a generalization of the bounded confidence rules [3,4], as those rules can be recovered as special cases.…”
Section: The Sznajd Model With Confidence Rulesmentioning
confidence: 99%
“…Previous research showed that physical cleansing does not only remove dirt from the body but that it also affects moral judgments (Schnall, Benton, & Harvey, 2008;Zhong et al, 2010), one's moral self-image (Zhong et al, 2010) and moral behavior (Reuven et al, 2014), as well as several other mental functions such as decision making (Xu et al, 2012), justification of recent choices (Lee & Schwarz, 2010b), optimism (Kaspar, 2013a), and product evaluation (Florack et al, 2014). Based on the assumption that all these effects are grounded on a specific (re-)weighting of cognitive information by the act of physical cleansing, we extended the hitherto scope to memory for (im)moral items.…”
Section: Discussionmentioning
confidence: 99%
“…Florack, Kleber, Busch, and Stöhr (2014) used hand washing to reduce consumers' biased perception of product features derived from ownership. Lee and Schwarz (2010b) showed that physical purity can reduce post-decisional dissonance as participants showed a reduced need to devaluate non-chosen options after hand washing. Finally, Kaspar (2013a) found an increased optimism regarding future performance in an anagram task when participants washed their hands after they had experienced failure in a preceding anagram task.…”
Section: Physical Cleansing and The Clean Slate Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Our paper clearly suggests one way in which dissonance can trigger unethical behavior. However, many questions regarding the role of motivated moral reasoning in the reduction of dissonance after an unethical act (Barkan, Ayal, Gino, & Ariely, 2012;Ditto, Pizarro, & Tannenbaum, 2009), how post-decisional dissonance can be reduced behaviorally (Lee & Schwarz, 2010), or how dissonance might trigger moral development as well as moral violations (Rholes, Bailey, & McMillan, 1982) remain open. As a field, we have only scratched the surface in terms of the role that cognitive dissonance plays in unethical behavior.…”
Section: Discussionmentioning
confidence: 99%